Influence of tree canopy on N2 fixation by pasture legumes and soil rhizobial abundance in Mediterranean oak woodlands. - Carranca, C.; Castro, I. V.; Figueiredo, N.; Redondo, R.; Rodrigues, a R. F.; Saraiva, I.; Maricato, R.; Madeira, M. a V. (The Science of the total environment, 2015)
Symbiotic N2 fixation is of primordial significance in sustainable agro-forestry management as it allows reducing the use of mineral N in the production of mixed stands and by protecting the soils from degradation. Thereby, on a 2-year basis, N2 fixation was evaluated in four oak woodlands under Mediterranean conditions using a split-plot design and three replicates. (15)N technique was used for determination of N2 fixation rate. Variations in environmental conditions (temperature, rainfall, radiation) by the cork tree canopy as well as the age of stands and pasture management can cause great differences in vegetation growth, legume N2 fixation, and soil rhizobial abundance. In the present study, non-legumes dominated the swards, in particular beneath the tree canopy, and legumes represented only 42% of total herbage. A 2-fold biomass reduction was observed in the oldest sown pasture in relation to the medium-age sward (6tDWha(-1)yr(-1)). Overall, competition of pasture growth for light was negligible, but soil rhizobial abundance and symbiotic N2 fixation capacity were highly favored by this environmental factor in the spring and outside the influence of tree canopy. Nitrogen derived from the atmosphere was moderate to high (54-72%) in unsown and sown swards. Inputs of fixed N2 increased from winter to spring due to more favorable climatic conditions (temperature and light intensity) for both rhizobia and vegetation growths. Assuming a constant fixation rate at each seasonal period, N2 fixation capacity increased from about 0.10kgNha(-1) per day in the autumn-winter period to 0.15kgNha(-1) per day in spring. Belowground plant material contributed to 11% of accumulated N in pasture legumes and was not affected by canopy. Size of soil fixing bacteria contributed little to explain pasture legumes N.
The following values have no corresponding Zotero field: publisher: Elsevier B.V. accession-num: 25460942
Keywords: Above and belowground organ; Agro forestry system; Cutting frequency; light; Quercus Suber L